Distributed Event-Triggered Impulsive Control for Synchronization of Coupled Harmonic Oscillators - Ma, Guodong; Ren, Jie; Liu, Yansen; Lu, Guoping (IEEE access, 2021)
This paper addresses the synchronization problem of coupled harmonic oscillators via event-triggered impulsive control. Different from the existing results where both position and velocity measurements are required to achieve the synchronization, two kinds of event-triggered impulsive mechanisms, that is, the position-only and velocity-only approaches are proposed respectively, which effectively extends the event-triggered impulsive control strategy to the synchronization problem with limited information. Sufficient conditions are proposed to exhibit the convergence behavior of the coupled harmonic oscillators. Meanwhile, it is derived that Zeno behavior can be excluded by using the designed controller. Two simulation examples are illustrated to substantiate the performance of the proposed synchronization protocols.